Defects and Improvement of Predicting Mine Water Inflow by Virtual Large Diameter Well Method. (22nd September 2022) - Xu, Zhimin; Chen, Tianci; Li, Jianfeng; Sun, Yajun; Zhang, Chenghang; Chen, Ge; Gao, Yating; He, Ye
Abstract : In order to prevent the occurrence of water inrush accidents, it is particularly important to predict the mine water inrush, especially the accurate prediction of the mine water inflow in the coal mining process. Mine water inflow is caused by mining disturbance, groundwater flows into mining panels along the mining-induced fissures, and a depression cone of water table is formed in certain range around the mining sites. Mining panel is usually regarded as an irregular "virtual large diameter well" so as to calculate mine water inflow in China. However, in the mining process, the area, shape, and cross section of goafs are constantly changing, so is the water inflow. Therefore, the central position and influence radius of the "virtual large diameter well" in the spatial and temporal distribution are in a dynamic process of continuous movement and expansion, rather than being confined to a static position. This paper firstly analyzes the formation mechanism of coal mine roof water inflow and the errors and defects in the calculation of mine water inflow by virtual large diameter well (VLDWM). Then, based on the theory of steady flow and combined with the dynamic change process of goaf area and depression cone of water table during mining activities, this paper proposes an improved method and puts forward a concept of dynamic virtual large diameter well (DVLDWM) and establishes a theoretical model of the central position and influence radius of the "mining large diameter well" moving forward. The first (periodic) caving step is taken as the calculation unit and generalized as the "dynamic large diameter well, " which is used to calculate the dynamic water inflow in the process of mine advancing. Taking the No.7208 mining panel in Zhangshuanglou Coalmine in Xuzhou City, Jiangsu Province, as the study area, the mine water inflow was calculated dynamically by using the DVLDWM. The results show that the mine water inflow calculated is similar to the actual mine water inflow of the No.7208 mining panel observed, thus proving the reliability and credibility of the DVLDWM.